ANALISIS PENGELOLAAN LIMBAH CAIR USAHA LAUNDRY - Yusmidiarti, Yusmidiarti (Politeknik Kesehatan Kemenkes Bengkulu, 2016)
Washing clothes and other household appliances (laundry) is one ofbusinesses that ease the burden on society in terms of domesticity. Urban communities,especially those having activities outside home are relatively dense prefer to takeadvantage of laundry services. The appearance of the laundry business is to provide theadvantages and the solutions on household work, also provide new jobs for people in thesurrounding area. But advantage gained is inversely proportional to the quality ofresulting environment. The proliferation of laundry services will worsen the quality ofthe surrounding water because this business is not equipped with waste treatmentprocesses but is discharged directly into sewers or water bodies nearby. As a result oflaundry waste discharged into water bodies continuously without being processed, it maycause water pollution problems. The result of research that gained in the implementationof waste management obligations by some laundry business in Bengkulu city asmeticulous in environmental pollution control measures, has not done well and the lackof awareness and knowledge about the dangers of toxic waste generated laundry businessand the lack of government attention to the laundry business growth impact in BengkuluCity.